Catheter ablation of atrial fibrillation and atrial tachycardia in patients with pulmonary hypertension: a randomized study - Havranek, Stepan; Fingrova, Zdenka; Skala, Tomas; Reichenbach, Adrian; Dusik, Milan; Jansa, Pavel; Ambroz, David; Dytrych, Vladimir; Klimes, Dalibor; Hutyra, Martin; Kautzner, Josef; Linhart, Ales; et al. (Europace, 2023)
AIMS: Atrial fibrillation (AF), typical atrial flutter (AFL), and other atrial tachycardias (ATs) are common in patients with pulmonary hypertension. Frequently, several supraventricular arrhythmias are successively observed in individual patients. We investigated the hypothesis of whether more extensive radiofrequency catheter ablation of the bi-atrial arrhythmogenic substrate instead of clinical arrhythmia ablation alone results in superior clinical outcomes in patients with pulmonary arterial hypertension (PH) and supraventricular arrhythmias. METHODS AND RESULTS: Patients with combined post- and pre-capillary or isolated pre-capillary PH and supraventricular arrhythmia indicated to catheter ablation were enrolled in three centres and randomized 1:1 into two parallel treatment arms. Patients underwent either clinical arrhythmia ablation only (Limited ablation group) or clinical arrhythmia plus substrate-based ablation (Extended ablation group). The primary endpoint was arrhythmia recurrence >30 s without antiarrhythmic drugs after the 3-month blanking period. A total of 77 patients (mean age 67 ± 10 years; 41 males) were enrolled. The presumable clinical arrhythmia was AF in 38 and AT in 36 patients, including typical AFL in 23 patients. During the median follow-up period of 13 (interquartile range: 12; 19) months, the primary endpoint occurred in 15 patients (42%) vs. 17 patients (45%) in the Extended vs. Limited ablation group (hazard ratio: 0.97, 95% confidence interval: 0.49-2.0). There was no excess of procedural complications and clinical follow-up events including an all-cause death in the Extended ablation group. CONCLUSION: Extensive ablation, compared with a limited approach, was not beneficial in terms of arrhythmia recurrence in patients with AF/AT and PH. CLINICAL TRIALS REGISTRATION: ClinicalTrials.gov; NCT04053361.
Keywords: Pulmonary hypertension; Atrial fibrillation; Catheter ablation; Atrial tachycardia